Pengaruh Total Quality Management terhadap Kinerja Karyawan CV Bima Utama - Puspito, Febryan; Rosalina, Sylvia Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
In this era of globalization, business growth in Indonesia has increased significantly. This is indicated by the large number of businesses in Indonesia. Companies need to create an appropriate performance measurement system to determine the characteristics and quality of performance and identify actions that can be taken in an effort to increase employee work productivity. Therefore, to improve employee performance, companies can apply elements of Total Quality Management (TQM). The method used in this research is quantitative by distributing questionnaires. The research sampling technique uses non- probability sampling with a saturated sampling method. The sample used in this research was 37 respondents. The results of this research show that based on the results of the research that has been conducted it is known that customer focus has a positive and insignificant effect on employee performance, continuous improvement has a positive and insignificant effect on employee performance and education and training has a significant positive effect on employee performance.